Self efficacy terhadap quarter life crisis pada mahasiswa - Wulandari, Amila Suci; Suroso, Suroso; Arifiana, Isrida Yul (Faculty of Psychology Universitas 17 Agustus 1945 Surabaya, 2024)
Abstract The aim of this study is to analyze the relationship between self-efficacy and quarter-life crisis among students at the 17 Agustus 1945 University in Surabaya. The sampling method used in this study is purposive sampling, where the researcher sets the criteria that the respondents must be active students from the 2020 cohort who are preparing their theses. Data were obtained from 294 students from the 2020 cohort at the 17 Agustus 1945 University in Surabaya who were in the process of writing their theses. This study obtained a correlation value of -0.265 using the Spearman’s Rho analysis technique with the Statistical Package for the Social Sciences (SPSS) version 25 for Windows. The hypothesis stating that there is a negative relationship between self-efficacy and quarter-life crisis among students is accepted in this study. This means that the higher the level of self-efficacy a student has, the lower the likelihood of experiencing a quarter-life crisis. Abstrak Tujuan penelitian ini adalah menganalisis adanya hubungan antara Self efficacy dengan Quarter life crisis pada mahasiswa Universitas 17 Agutus Surabaya. Metode pengambilan sampel yang digunakan dalam penelitian ini adalah purposive sampling, dimana peneliti menetapkan kriteria bahwa responden harus merupakan mahasiswa aktif angkatan 2020 yang sedang menyiapkan skripsi. Data diperoleh 294 mahasiswa angkatan 2020 Universitas 17 Agustus 1945 Surabaya yang sedang memprogram skripsi. Penelitian ini memperoleh nilai korelasi -0,265 menggunakan teknik analisis Spearman’s Rho dengan program Statistic for Social Science for windows (SPSS) versi 25 IBM for Windows. Dalam penelitian ini, hipotesis yang menyatakan bahwa terdapat hubungan negatif antara tingkat self-efficacy dengan tingkat quarter-life crisis pada mahasiswa dapat diterima. Artinya, semakin tinggi tingkat self-efficacy yang dimiliki mahasiswa, maka kemungkinan mengalami quarter-life crisis akan semakin rendah.